A method for preparing a degradable anti-slip mat
By using thermoplastic polyurethane elastomers and other materials, a degradable anti-slip pad is prepared, which solves the problems of high price, poor anti-slip performance and difficult degradation of existing anti-slip pads, and achieves efficient anti-slip and excellent environmental protection performance.
Patent Information
- Application Number
- CN202410697023.6
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2024-05-31
- Publication Date
- 2025-04-08
- Estimated Expiration
- 2044-05-31
AI Technical Summary
The existing anti-slip pads have the disadvantages of high price, poor anti-slip performance, easy release of harmful gases during processing, and difficult degradation, and cannot meet environmental protection and performance needs.
Thermoplastic polyurethane elastomer, fillers, antioxidants, anti-slip pellets and adhesives are used to mix and laminate through high-speed shearing machines to prepare a degradable anti-slip pad with excellent environmental protection performance and efficient anti-slip function.
It significantly improves the wear resistance and anti-slip performance of the anti-slip pad, with a degradation cycle of only 56 days, and has excellent environmental protection performance and a long service life.
Smart Images

Figure BDA0004870027450000061 
Figure BDA0004870027450000071
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of anti-skid pads, in particular to a method for preparing a degradable anti-skid pad. Background Art
[0002] According to the material, the anti-skid mat can be divided into: rubber anti-skid mat, PVC anti-skid mat, PU anti-skid mat, AB glue anti-skid mat, silicone anti-skid mat, magic glue anti-skid mat, etc. As people's environmental awareness becomes stronger and stronger, the attention to the degradation difficulty of anti-skid mat is also increasing. Using TPU to replace PVC and other materials to produce anti-skid mats accelerates the degradation rate of waste products, while having excellent environmental protection characteristics, is a research hotspot for sustainable development.
[0003] Chinese patent CN113072754A: relates to the technical field of rubber anti-skid mats, specifically to a degradable anti-skid mat and its preparation method. The degradable anti-skid mat of the present invention uses natural rubber as the main raw material, and adds silicone modified rubber, modified plant fiber, ultraviolet absorber, antioxidant, silane coupling agent, accelerator, sodium bicarbonate and lubricant.
[0004] Chinese patent CN107841068A: relates to the field of anti-skid mat materials, specifically to microporous foamed degradable anti-skid mats and preparation methods thereof. The microporous foamed degradable anti-skid mat is prepared from the following raw materials in parts by weight: 100 parts of polyvinyl chloride, 70-80 parts of dioctyl terephthalate, 5-15 parts of nitrile rubber, 5-20 parts of straw powder, 2-10 parts of filler, 2-5 parts of stabilizer, 0.3-0.8 parts of antioxidant, 0.3-1 parts of ultraviolet absorber, 0.5-2 parts of foaming agent, 0.1-0.5 parts of microsphere expansion agent, and 0.1-1 parts of lubricant.
[0005] Chinese patent CN102873948A: relates to a new type of environmentally friendly anti-skid mat, including a colloid, characterized in that: the colloid is composed of five layers: an anti-skid layer, a glue layer, a coloring layer, a glue layer, and an inner lining layer; the anti-skid layer has concave-convex stripes on its surface, and the concave-convex stripes are filled with nano-air, which is a polyvinyl chloride resin layer with anti-skid ions and a light transmittance of more than 70% to 85%; the glue layer is a waterproof adhesive layer of a polymer transparent material; the coloring layer is an acrylonitrile-styrene-vinyl chloride copolymer layer; the inner lining layer is a film lining; it can be arbitrarily cut according to the size and shape of bathrooms, shower rooms, bathtubs, etc.
[0006] The anti-skid mats prepared by the above patents and prior art have the disadvantages of high price, poor anti-skid performance, easy release of harmful gases during processing, and difficulty in degradation. Summary of the invention
[0007] The present invention aims to solve the above technical problems at least to a certain extent.
[0008] The purpose of the present invention is to prepare a degradable anti-skid mat with excellent environmental performance. In addition, the anti-skid mat is enhanced to maintain a high-efficiency anti-skid function in a wet or greasy environment.
[0009] The technical solution adopted by the present invention to solve its technical problem is:
[0010] A method for preparing a degradable anti-slip mat, the operating steps are:
[0011] S1: Add 50-60 parts of thermoplastic polyurethane elastomer and 10-20 parts of filler by weight into a high-speed shearing machine, and mix and stir for 5-10 minutes;
[0012] S2: Add 1-5 parts of antioxidant and 1-5 parts of anti-slip granules, and continue mixing and stirring for 10-20 minutes;
[0013] S3: Add 1-5 parts of adhesive and continue stirring for 10-20 minutes to obtain a degradable anti-slip mat material;
[0014] S4: laminating the degradable anti-skid mat material into sheets at 160-180° C., and punching and forming the sheets to obtain the degradable anti-skid mat.
[0015] In one embodiment, the filler is one of calcium carbonate, magnesium hydroxide and silicon dioxide.
[0016] In one embodiment, the rotation speed of the high-speed shearing machine is 800-1000 rpm.
[0017] In one embodiment, the antioxidant is one of diaryl secondary amine and p-phenylenediamine.
[0018] In one embodiment, the anti-slip granular material is one of ceramic particles, corundum, and basalt.
[0019] In one embodiment, the preparation method of the adhesive is:
[0020] H1: 5-10 parts of polylactic acid with an average molecular weight of 4000-5000 g / mol, 200-300 parts of dry toluene, 3-6 parts of octadecyl dihydroxyethyl betaine, and 1-3 parts of tetrabutyl titanate are mixed, and stirred at a temperature of 100-120° C. for 2-5 hours to cause an esterification reaction;
[0021] H2: Add 30-40 parts of polyol, 30-45 parts of 4,4'-diphenylmethane diisocyanate, 14-28 parts of ethyl isocyanate acrylate, and 1-4 parts of stannous octoate, introduce dry nitrogen to remove air from the system, and heat under reflux for 2-4 hours under stirring to carry out polycondensation reaction;
[0022] H3: Continue to add 0.005-0.03 parts of 4-vinylpyridine-nickel and 0.05-0.3 parts of (ferrocenyl)hexanethiol, stir and react at a temperature of 100-120°C for 2-5 hours to carry out an addition reaction. After the reaction is completed, remove toluene and other impurities by reduced pressure distillation to obtain an adhesive.
[0023] In one embodiment, the polyol is one of ethylene glycol, propylene glycol, glycerol, isopropanol, and pentaerythritol.
[0024] Reaction mechanism
[0025] Betaine, as a zwitterionic compound, imparts specific biocompatibility to polyurethane materials through the zwitterions of sulfobetaine; the pyridine-nickel complex participates in the addition reaction in this reaction system to promote the reaction of sulfur-containing compounds with polyurethane chains; the nickel on the pyridine ring may reduce the reaction energy barrier and accelerate the reaction process by coordinating with the reaction intermediates; the addition of (ferrocenyl) hexanethiol not only provides a thiol (-SH) group to participate in the click chemistry reaction, but also contributes to the mechanical properties of the polyurethane material; the introduction of this metal organic group can increase the functionality of the material and improve the mechanical strength of the material.
[0026] Due to the introduction of betaine and other functional groups, the crosslinking density and network structure of the polyurethane adhesive are optimized, which significantly improves the wear resistance of the material; this means that the adhesive coating can withstand continuous physical wear and extend the service life of the anti-slip mat.
[0027] The polyurethane material itself has good waterproof and oil-resistant properties. The introduction of groups such as betaine further enhances this property, allowing the anti-slip mat to maintain high anti-slip function even in a humid or greasy environment.
[0028] Through the above steps, an adhesive with specific chemical structure and properties can be prepared, which is suitable for surface bonding of various materials.
[0029] Technical Effects
[0030] 1. The adhesive prepared by the present invention can significantly improve the wear resistance of the anti-skid pad, thereby ensuring the anti-skid effect of the anti-skid pad;
[0031] 2. The present invention adopts thermoplastic polyurethane elastomer to prepare the degradable anti-skid mat, and the material itself is a mature environmentally friendly material, which is degradable and non-toxic when burned. The degradable anti-skid mat prepared by the present invention has a degradation period of only 56 days and has excellent environmental performance. DETAILED DESCRIPTION
[0032] The technical solution of the present invention is further described below in conjunction with the embodiments, but is not limited thereto. Any modification or equivalent replacement of the technical solution of the present invention without departing from the spirit and scope of the technical solution of the present invention should be included in the protection scope of the present invention.
[0033] Example 1
[0034] A method for preparing a degradable anti-slip mat, the operating steps are:
[0035] S1: Add 50g of thermoplastic polyurethane elastomer and 10g of filler into a high-speed shearing machine and mix and stir for 5min;
[0036] S2: Add 1g antioxidant and 1g anti-slip granules, and continue mixing and stirring for 10min;
[0037] S3: Add 1 g of adhesive and continue stirring for 10 min to obtain a degradable anti-slip mat material;
[0038] S4: laminating the degradable anti-skid mat material into sheets at 160° C., and punching and forming the sheets to obtain the degradable anti-skid mat.
[0039] The filler is calcium carbonate.
[0040] The rotating speed of the high-speed shearing machine is 800 rpm.
[0041] The antioxidant is a diaryl secondary amine.
[0042] The anti-skid granules are ceramic particles.
[0043] The preparation method of the adhesive is:
[0044] H1: 5 g of polylactic acid with an average molecular weight of 4000 g / mol, 200 g of dry toluene, 3 g of octadecyl dihydroxyethyl betaine, and 1 g of tetrabutyl titanate were mixed and stirred at 100° C. for 2 hours to cause an esterification reaction;
[0045] H2: Add 30 g of polyol, 30 g of 4,4'-diphenylmethane diisocyanate, 14 g of ethyl isocyanate acrylate, and 1 g of stannous octoate, introduce dry nitrogen to remove air from the system, and heat under reflux for 2 hours under stirring to carry out polycondensation reaction;
[0046] H3: Continue to add 0.005 g of 4-vinylpyridine-nickel and 0.05 g of (ferrocenyl)hexanethiol, and stir the reaction at 100°C for 2 hours to carry out an addition reaction. After the reaction is completed, toluene and other impurities are removed by reduced pressure distillation to obtain an adhesive.
[0047] The polyol is ethylene glycol.
[0048] Example 2
[0049] A method for preparing a degradable anti-slip mat, the operating steps are:
[0050] S1: Add 53g of thermoplastic polyurethane elastomer and 13g of filler into a high-speed shearing machine and mix and stir for 6min;
[0051] S2: Add 2g antioxidant and 2g anti-slip granules, and continue mixing and stirring for 15min;
[0052] S3: adding 2 g of adhesive and continuing stirring for 5 min to obtain a degradable anti-slip mat material;
[0053] S4: laminating the degradable anti-skid mat material into sheets at 165° C., and punching and forming the sheets to obtain the degradable anti-skid mat.
[0054] The filler is magnesium hydroxide.
[0055] The rotating speed of the high-speed shearing machine is 850 rpm.
[0056] The antioxidant is a diaryl secondary amine.
[0057] The anti-skid granular material is corundum.
[0058] The preparation method of the adhesive is:
[0059] H1: 6 g of polylactic acid with an average molecular weight of 4300 g / mol, 240 g of dry toluene, 4 g of octadecyl dihydroxyethyl betaine, and 2 g of tetrabutyl titanate were mixed and stirred at 105° C. for 3 hours to cause an esterification reaction;
[0060] H2: 33 g of polyol, 35 g of 4,4'-diphenylmethane diisocyanate, 20 g of ethyl isocyanate acrylate, and 2 g of stannous octoate were added, dry nitrogen was introduced to remove air from the system, and the mixture was heated under reflux for 3 hours under stirring to carry out polycondensation reaction;
[0061] H3: Continue to add 0.01 g of 4-vinylpyridine-nickel and 0.1 g of (ferrocenyl)hexanethiol, and stir the reaction at 105°C for 3 hours to carry out an addition reaction. After the reaction is completed, toluene and other impurities are removed by reduced pressure distillation to obtain an adhesive.
[0062] The polyol is propylene glycol.
[0063] Example 3
[0064] A method for preparing a degradable anti-slip mat, the operating steps are:
[0065] S1: Add 58g of thermoplastic polyurethane elastomer and 18g of filler into a high-speed shearing machine and mix and stir for 9 minutes;
[0066] S2: Add 4g antioxidant and 4g anti-slip granules, and continue mixing and stirring for 15min;
[0067] S3: Add 4 g of adhesive and continue stirring for 15 min to obtain a degradable anti-slip mat material;
[0068] S4: laminating the degradable anti-skid mat material into sheets at 175° C., and punching and forming the sheets to obtain the degradable anti-skid mat.
[0069] The filler is magnesium hydroxide.
[0070] The rotating speed of the high-speed shearing machine is 950 rpm.
[0071] The antioxidant is p-phenylenediamine.
[0072] The anti-skid granular material is corundum.
[0073] The preparation method of the adhesive is:
[0074] H1: 9 g of polylactic acid with an average molecular weight of 4800 g / mol, 280 g of dry toluene, 5 g of octadecyl dihydroxyethyl betaine, and 2 g of tetrabutyl titanate were mixed and stirred at 115° C. for 4 hours to cause an esterification reaction;
[0075] H2: 38 g of polyol, 40 g of 4,4'-diphenylmethane diisocyanate, 25 g of ethyl isocyanate acrylate, and 3 g of stannous octoate were added, dry nitrogen was introduced to remove air from the system, and the mixture was heated under reflux for 3 hours under stirring to carry out polycondensation reaction;
[0076] H3: Continue to add 0.02 g of 4-vinylpyridine-nickel and 0.2 g of (ferrocenyl)hexanethiol, stir and react at a temperature of 115°C for 4 hours to carry out an addition reaction. After the reaction is completed, toluene and other impurities are removed by reduced pressure distillation to obtain an adhesive.
[0077] The polyol is glycerol.
[0078] Example 4
[0079] A method for preparing a degradable anti-slip mat, the operating steps are:
[0080] S1: Add 60g of thermoplastic polyurethane elastomer and 20g of filler into a high-speed shearing machine and mix and stir for 10min;
[0081] S2: Add 5g antioxidant and 5g anti-slip granules, and continue mixing and stirring for 20min;
[0082] S3: Add 5 g of adhesive and continue stirring for 20 min to obtain a degradable anti-slip mat material;
[0083] S4: laminating the degradable anti-skid mat material into sheets at 180° C., and punching and forming the sheets to obtain the degradable anti-skid mat.
[0084] The filler is silicon dioxide.
[0085] The rotating speed of the high-speed shearing machine is 1000 rpm.
[0086] The antioxidant is p-phenylenediamine.
[0087] The anti-slip granular material is basalt.
[0088] The preparation method of the adhesive is:
[0089] H1: 10 g of polylactic acid with an average molecular weight of 5000 g / mol, 300 g of dry toluene, 6 g of octadecyl dihydroxyethyl betaine, and 3 g of tetrabutyl titanate were mixed and stirred at 120° C. for 5 hours to cause an esterification reaction;
[0090] H2: 40 g of polyol, 45 g of 4,4'-diphenylmethane diisocyanate, 28 g of ethyl isocyanate acrylate, and 4 g of stannous octoate were added, dry nitrogen was introduced to remove air from the system, and the mixture was heated under reflux for 4 hours under stirring to carry out polycondensation reaction;
[0091] H3: Continue to add 0.03 g of 4-vinylpyridine-nickel and 0.3 g of (ferrocenyl)hexanethiol, stir and react at 120°C for 5 hours to carry out an addition reaction. After the reaction is completed, remove toluene and other impurities by vacuum distillation to obtain an adhesive.
[0092] The polyol is pentaerythritol.
[0093] Comparative Example 1
[0094] This example is the same as Example 1 except that octadecyl dihydroxyethyl betaine is not added.
[0095] Comparative Example 2
[0096] This example is the same as Example 1 except that 4,4'-diphenylmethane diisocyanate is not added.
[0097] Comparative Example 3
[0098] This example is the same as Example 1 except that (ferrocenyl) hexanethiol is not added.
[0099] Test method:
[0100] 1. Friction coefficient: Refer to the method of GB / T3903.6-2005 to test the static friction coefficient of dry friction;
[0101] 2. Degradation conditions: ambient humidity 65%, ambient temperature 70℃.
[0102] Test results:
[0103]
[0104]
[0105] The adhesive prepared by the present invention can significantly improve the wear resistance of the anti-skid pad; the degradable anti-skid pad prepared by the present invention has a degradation period of only 56 days and has excellent environmental protection performance.
[0106] Those skilled in the art may make various modifications and alterations without departing from the spirit and scope of the present invention. Therefore, the scope of protection of the present invention shall be determined by the claims.
Claims
1. A method for preparing a degradable anti-slip mat, the operating steps of which are: S1: Add 50-60 parts of thermoplastic polyurethane elastomer and 10-20 parts of filler by weight into a high-speed shearing machine, and mix and stir for 5-10 minutes; S2: Add 1-5 parts of antioxidant and 1-5 parts of anti-slip granules, and continue mixing and stirring for 10-20 minutes; S3: Add 1-5 parts of adhesive and continue stirring for 10-20 minutes to obtain a degradable anti-slip mat material; S4: laminating the degradable anti-skid mat material into sheets at 160-180° C., and punching and forming the sheets to obtain the degradable anti-skid mat; The preparation method of the adhesive is: H1: 5-10 parts of polylactic acid with an average molecular weight of 4000-5000 g / mol, 200-300 parts of dry toluene, 3-6 parts of octadecyl dihydroxyethyl betaine, and 1-3 parts of tetrabutyl titanate are mixed, and stirred at a temperature of 100-120° C. for 2-5 hours to cause an esterification reaction; H2: Add 30-40 parts of polyol, 30-45 parts of 4,4'-diphenylmethane diisocyanate, 14-28 parts of ethyl isocyanate acrylate, and 1-4 parts of stannous octoate, introduce dry nitrogen to remove air from the system, and heat under reflux for 2-4 hours under stirring to carry out polycondensation reaction; H3: Continue to add 0.005-0.03 parts of 4-vinylpyridine-nickel and 0.05-0.3 parts of (ferrocenyl)hexanethiol, stir and react at a temperature of 100-120°C for 2-5 hours to carry out an addition reaction. After the reaction is completed, remove toluene and other impurities by reduced pressure distillation to obtain an adhesive.
2. The method for preparing a degradable anti-slip mat according to claim 1, characterized in that: The filler is one of calcium carbonate, magnesium hydroxide and silicon dioxide.
3. The method for preparing a degradable anti-slip mat according to claim 1, characterized in that: The rotation speed of the high-speed shearing machine is 800-1000 rpm.
4. The method for preparing a degradable anti-slip mat according to claim 1, characterized in that: The antioxidant is a diaryl secondary amine.
5. The method for preparing a degradable anti-slip mat according to claim 1, characterized in that: The anti-skid granular material is one of ceramic particles, corundum and basalt.
6. The method for preparing a degradable anti-slip mat according to claim 1, characterized in that: The polyol is one of ethylene glycol, propylene glycol, glycerol and pentaerythritol.
Citation Information
Patent Citations
Novel environment-friendly non-slip mat and preparation method thereof
CN102873948A
Microcellular foaming degradable non-slip mat and preparation method thereof
CN107841068A
Degradable non-slip mat and preparation method thereof
CN113072754A
Force-induced responsive supramolecular polymer
CN111378179A
Polylactic acid composition and preparation method thereof
CN114773581A